Chinese Herbal Medicine, Jian Pi Li Gan Decoction, Improved Survival of Nonresectable Hepatocellular Cancer After Radiofrequency Ablation: A Retrospective Study. (June 2018) - Tang, Chengwu; Feng, Wenming; Qin, Lianjin; Bao, Ying
Objective: To observe the effect of Jian Pi Li Gan Decoction (JPLGD) on long-term survival of nonresectable hepatocellular cancer (HCC) after radiofrequency ablation (RFA).Methods: Between January 2010 and February 2013, 95 patients with nonresectable HCC treated by RFA in our hospital were enrolled, of whom 47 patients received JPLGD accompanying RFA (JPLGD group), and 48 patients received RFA alone (control group). Medical records of these patients were retrospectively analyzed. Long-term survival, complication, and treatment event were compared.Results: Baseline characteristics did not differ between the 2 groups. No significant adverse effects or toxicities related to herbal medicine were found. The JPLGD group had significantly less liver failure (3/47 vs 10/48, P = .0405) and a higher treatment success rate than the control group (44/47 vs 37/48, P = .0230). The 3-year overall survival probability was significantly higher in the JPLGD group ( P = .0175).Conclusion: JPLGD has the potential to effectively and safely improve long-term survival of nonresectable HCC by increasing treatment success of RFA.